2015
DOI: 10.1177/0907568215602319
|View full text |Cite
|
Sign up to set email alerts
|

Blood binds: Confronting the moral and political economies of orphanhood and adoption in Uganda

Abstract: Strong extended-family fostering traditions and beliefs about "blood" as a substance that not only binds kin but also carries pathogens like HIV and certain character traits make formal adoption of unrelated children rare. Even so, there is strong public sentiment against the increasing number of foreigners seeking to adopt Ugandan children in the wake of other African countries closing adoption programs. Institutionalized orphans are thus in a double "blood bind,"-where, on one hand, they are nobody's childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Meanwhile, there have been some efforts to encourage domestic adoption for children without parental care, as stipulated by the United Nations Guidelines for the Alternative Care of Children (United Nations General Assembly, 2010) and The Hague Convention on Intercountry Adoption (Hague Conference on Private International Law 1993). Despite a long tradition of kinship care, fostering, and child circulation, many Ugandans have been reluctant to embrace formal adoption practices, especially of unrelated children (Cheney, 2015). So, in 2013, MGLSD and Child’s i Foundation launched a nationwide media campaign called Ugandans Adopt .…”
Section: Fighting Back Against Adoption Corruptionmentioning
confidence: 99%
“…Meanwhile, there have been some efforts to encourage domestic adoption for children without parental care, as stipulated by the United Nations Guidelines for the Alternative Care of Children (United Nations General Assembly, 2010) and The Hague Convention on Intercountry Adoption (Hague Conference on Private International Law 1993). Despite a long tradition of kinship care, fostering, and child circulation, many Ugandans have been reluctant to embrace formal adoption practices, especially of unrelated children (Cheney, 2015). So, in 2013, MGLSD and Child’s i Foundation launched a nationwide media campaign called Ugandans Adopt .…”
Section: Fighting Back Against Adoption Corruptionmentioning
confidence: 99%
“…Instead, it drove the establishment of orphanages to meet the demand of funding, rather than to address the needs of orphans (Cheney, 2014b). She found that foreign donors were instructing their partner orphanages to increase the numbers of children living in the orphanages to meet their supporters' expectations (Cheney, 2015). Therefore, whilst the express intent of the orphan industrial complex is to respond to children in need, in reality it has the reverse effect with children being touted as orphans for purposes of profit and status (Cheney, 2015).…”
Section: The Orphan Industrial Complexmentioning
confidence: 99%
“…She found that foreign donors were instructing their partner orphanages to increase the numbers of children living in the orphanages to meet their supporters' expectations (Cheney, 2015). Therefore, whilst the express intent of the orphan industrial complex is to respond to children in need, in reality it has the reverse effect with children being touted as orphans for purposes of profit and status (Cheney, 2015). Cantwell and Gillioz (2018, p. 6) agree that the act of voluntourism "reinforces the orphan myth among foreigners who are unaware that they are basically contributing to a system which tears children away from their families for financial gain".…”
Section: The Orphan Industrial Complexmentioning
confidence: 99%
“…As Kim (2007b, p. 135) reported of Korean adoptions, strong economic and political relationships with the US create a 'fever' of all things American so much so that 'whoever goes to America, his or her life will be better off', a belief common in developing countries. This combines with a parallel belief held by prospective parents that life is better in the west and political discourse that seeks to find a child for every home (Cheney, 2015).…”
Section: Fraud Lies and Money In Samoamentioning
confidence: 99%